Adaptation strategies for port infrastructure and facilities under climate change at the Kaohsiung port. (October 2020) - Yang, Yi-Chih; Ge, Ying-En
Abstract: The growing impact of climate change on port infrastructure and facilities currently may lead to a rising frequency of such serious natural disasters or accidents as rising sea level, increasing extreme weather, increasing intensity of tropical storms and typhoons, rising wave height surmounting breakwater design levels, heavy rain exceeding quay well drainage capacity, rising ocean temperatures, and deteriorating harbor water quality. The paper aims to apply a risk management matrix approach to vulnerability assessment and identification of desirable adaptation strategies. The data for this investigation is first collected by means of questionnaire survey of experts in shipping companies or port management offices at the Kaohsiung port. Then, a vulnerability analysis of port infrastructure and facilities is carried out under the impact of severe typhoons. Subsequently, adaptation strategies are identified for infrastructure and facilities at the Kaohsiung port to address the adverse impacts of climate change. One intellectual merit of this paper is that ten vulnerability assessment criteria are proposed for addressing the impacts of climate change on port infrastructure and facilities. Second, both ground and access roads in the port area, and drainage facilities in flooding-prone areas are shown to be damaged in the moderate risk areas potentially impacted by typhoons. The third merit is that a set of adaptation strategies has been identified for the moderate risk areas impacted by serious typhoons. Highlights: A risk management matrix approach is applied to assess vulnerability and identify desirable adaptation strategies. 10 vulnerability assessment criteria are given for solving impacts of climate change on port infrastructure and facilities. Both ground and access roads in the port area and drainage facilities in flooding-prone areas are shown to be damaged. A set of adaptation strategies has been identified for moderate risk areas impacted by serious typhoons.